2021
DOI: 10.1096/fj.202002278r
|View full text |Cite
|
Sign up to set email alerts
|

Lnc‐ing pluripotency maintenance and early differentiation in human pluripotent stem cells

Abstract: Pluripotency maintenance and lineage differentiation are two major characteristics of human embryonic and induced pluripotent stem cells. The determination of self-renewal or differentiation is under the exquisite control of the gene regulatory network, which is composed of transcription factors, signaling pathways, metabolic factors, chromatin or histone modifiers, miRNAs, and lncRNAs. Growing evidence has shown that long noncoding RNAs (lncRNAs) play important roles in epigenetic, transcriptional, and posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…ChAHP complex was shown to modulate spatial chromatin loop organization locally ( Kaaij et al, 2019 ), and plays essential roles in maintaining accurate cell fate decisions during development by regulating enhancer accessibility ( Arends et al, 2019 ; Ostapcuk et al, 2018 ; Zhao et al, 2017 ). Accumulating evidence suggested that long non-coding RNAs (lncRNAs) also play a role in positioning of chromatin binding enzymes, linking local transcriptions with chromatin binding factor recruitments ( Lu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…ChAHP complex was shown to modulate spatial chromatin loop organization locally ( Kaaij et al, 2019 ), and plays essential roles in maintaining accurate cell fate decisions during development by regulating enhancer accessibility ( Arends et al, 2019 ; Ostapcuk et al, 2018 ; Zhao et al, 2017 ). Accumulating evidence suggested that long non-coding RNAs (lncRNAs) also play a role in positioning of chromatin binding enzymes, linking local transcriptions with chromatin binding factor recruitments ( Lu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The long non-coding RNA (lncRNA) class includes long intergenic non-coding RNAs (lincRNAs), natural antisense transcripts (NATs), transcribed ultraconserved region (T-UCR) and non-coding pseudogenes. lncRNAs regulate stem-cell maintenance and cell differentiation, embryogenesis, X-chromosome inactivation, imprinting and the establishment of epigenetic marks [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stemness potential of pluripotent stem cells, as a critical factor in the regenerative field of tissue engineering, is influenced by certain specific lncRNAs 18,19) . Hoxa-AS3 is the first known lncRNA to inhibit the differentiation of MSCs into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%